Sweet8 bakery booking system - Basir, Nor Farhana; Kasim, Shahreen; Hassan, Rohayanti; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline Internasional Publishers, 2018)
Businesses that are promoted through social media Facebook are one of the smartest ways to increase sales of a product. Sweet8Bakery is a business operated by a private cake seller who runs a small cake business order. Sweet8Bakery seller also took this initiative as one of the ways to attract buyers. However, there are still some problems encountered such as booking information from customers still recorded through the manual method of bookkeeping. Therefore, the purpose of this project is to design a reservation system application to support the online system so that customer booking information can be managed properly. The development methodology for this system is the waterfall methodology in which it will be developed in stages and parallel to the phases found in the waterfall model. Adobe Dreamweaver CS6 is a web developer used with PHP programming language and is supported by Xampp's web server and MySQL database. The development of this system is to automate the manual system to a web-based system. In conclusion, at the end of this project a Sweet8Bakery reservation system will be built. With this system, it can help Sweet8Bakery customers to make cake reservations easier.